Ti65 titanium alloy welding material and design method and application thereof
By designing multiple groups of welding materials with different components and using vacuum non-consumable melting furnace and laser welding technology, the complex design and cost of titanium alloy welding materials are solved, and welding materials suitable for Ti65 titanium alloy are provided, realizing the More efficient welding performance and lower cost.
Patent Information
- Application Number
- CN202411272068.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing titanium alloy welding materials have long design cycles, high costs and complex processes. Moreover, Ti65 titanium alloys are prone to wear or cracks during long-term use, so it is necessary to develop welding materials suitable for their laser wire fill welding.
By determining the content of the base material element, designing multiple groups of welding materials with different components, using a vacuum non-consumable melting furnace for smelting, processing into long strips and laser welding, combining material simulation calculation and performance testing, appropriate welding materials are obtained Ti65 titanium alloy welding materials, including aluminum 6.5-7.5%, tin 4.5-5.5%, zirconium 3.0-7.0%, molybdenum 0.5-1.5%, silicon 0.2-0.5%, tantalum 1.5-2.5%, niobium 0.5-1.5%, tungsten 0.1-1.0%, the balance is titanium, and is used for laser wire fill welding of Ti65 titanium alloy.
It realizes faster, lower cost and simpler design of welding materials, improves the efficiency and performance of Ti65 titanium alloy welding and extends service life.
Smart Images

Figure CN119115302A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of welding materials, and in particular to a Ti65 titanium alloy welding material and a design method and application thereof. Background Art
[0002] Ti65 titanium alloy is a titanium alloy that can be used for a long time at 650℃, and is mainly used for engine rotors, blades and other parts. However, it is prone to wear or cracks during long-term use and needs to be repaired to extend its service life. Therefore, it is urgent to develop a welding material suitable for Ti65 titanium alloy laser wire welding.
[0003] In addition, the traditional titanium alloy welding material composition design needs to go through the processes of composition design, smelting, extrusion, drawing, welding, mechanical properties testing, etc., especially in the smelting, hot rolling, drawing, annealing stage, which requires a lot of manpower (many hours), material resources (raw materials, production equipment), and financial resources (large waste of resources), resulting in long cycle, high cost, and complex process of welding material design. Therefore, it is urgent to develop a titanium alloy welding material design method with short cycle, low cost, simple process and good performance. Summary of the invention
[0004] In view of the above problems, the present invention aims to provide a Ti65 titanium alloy welding material and a design method and application thereof.
[0005] The technical solution of the present invention is as follows:
[0006] On the one hand, a design method of a Ti65 titanium alloy welding material is provided, comprising the following steps:
[0007] S1: Determine the elements contained in the base material and the content of each element;
[0008] S2: designing a plurality of groups of welding material compositions with different compositions according to the parent material;
[0009] S3: using a vacuum non-consumable melting furnace to melt the welding material components to obtain multiple groups of titanium alloy ingots with different compositions;
[0010] S4: processing the titanium alloy ingot into a long strip, opening a groove on the parent material, and inserting the long strip into the groove for laser welding;
[0011] S5: Sampling the samples after laser welding and performing performance tests to obtain the performance of each weld joint, and according to the performance of each weld joint, selecting the welding material composition that is more suitable for the parent material to obtain the Ti65 titanium alloy welding material.
[0012] Preferably, in step S2, when designing the welding material composition, the elements contained in the welding material composition are all elements in the base material except element C.
[0013] Preferably, in step S2, when designing the welding material composition, the molecular dynamics, material properties, and equilibrium / non-equilibrium phase diagram of the material are simulated and calculated based on the software, so as to obtain the initial content of each element; then, a spectrometer is used to measure the element burnout during the welding process, and the initial content is corrected according to the measurement results.
[0014] Preferably, the software is one or more of Materials Studio, JmatPro, and Pandat.
[0015] Preferably, in step S4, the groove is formed by splicing two pieces of base materials with bevels.
[0016] Preferably, in step S5, when performing performance testing, the morphology, grain size and second phase morphology of the weld structure are observed using a metallographic microscope and a scanning electron microscope; the tensile properties and impact toughness of the sample are tested using a universal tensile machine and impact testing equipment to obtain the strength, plasticity and toughness values of the weld joint.
[0017] On the other hand, a Ti65 titanium alloy welding material is also provided, which is designed using the design method of the Ti65 titanium alloy welding material described in any one of the above. The designed composition includes, by mass percentage, 6.5-7.5% aluminum, 4.5-5.5% tin, 3.0-7.0% zirconium, 0.5-1.5% molybdenum, 0.2-0.5% silicon, 1.5-2.5% tantalum, 0.5-1.5% niobium, 0.1-1.0% tungsten, and the balance is titanium.
[0018] On the other hand, the application of the Ti65 titanium alloy welding material as described above in Ti65 titanium alloy laser wire welding is also provided.
[0019] Preferably, when performing laser wire welding, the speed is 30 mm / s, the power is 5 kW, the defocus is 0 mm, the laser circular swing diameter is 1.5 mm, and the swing frequency is 300 Hz.
[0020] The beneficial effects of the present invention are:
[0021] The present invention can design and obtain welding materials suitable for laser wire-filling welding of Ti65 titanium alloy more quickly, at a lower cost and in a simpler manner, thereby providing technical support for the welding of Ti65 titanium alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0023] Figure 1 It is a schematic diagram of the performance simulation calculation results of a titanium alloy with 0% Al content in a specific embodiment;
[0024] Figure 2 It is a schematic diagram of the performance simulation calculation results of a titanium alloy with 4% Al content in a specific embodiment;
[0025] Figure 3 It is a schematic diagram of the performance simulation calculation results of a titanium alloy with an Al content of 8% in a specific embodiment;
[0026] Figure 4 It is a schematic diagram of the phase types and contents of Ti-Al alloys with different Al contents in a specific embodiment;
[0027] Figure 5 It is a schematic diagram of the variation of phase content of titanium alloys with different Zr contents in a specific embodiment;
[0028] Figure 6 It is a schematic diagram of the variation of phase content of titanium alloys with different Si contents in a specific embodiment;
[0029] Figure 7 It is a schematic diagram of the variation of phase content of titanium alloys with different Mo contents in a specific embodiment;
[0030] Figure 8 It is a schematic diagram of the variation of phase content of titanium alloys with different Ta contents in a specific embodiment;
[0031] Fig. 9 It is a schematic diagram of the variation of phase content of titanium alloys with different Sn contents in a specific embodiment;
[0032] Fig.10 The weld metallographic organization diagrams of a specific embodiment and comparative examples 1-3 are shown;
[0033] Fig.11 It is a schematic diagram of the tensile curve results of the base material and the welded joint of a specific embodiment and comparative examples 1-3;
[0034] Fig.12 Schematic diagram of the hardness distribution results of the weld area of a specific embodiment and comparative examples 1-3. DETAILED DESCRIPTION
[0035] The present invention is further described below in conjunction with the accompanying drawings and embodiments. It should be noted that, in the absence of conflict, the embodiments in this application and the technical features in the embodiments can be combined with each other. It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as those generally understood by those of ordinary skill in the art to which this application belongs. The words "including" or "comprising" and the like used in the disclosure of the present invention mean that the elements or objects appearing before the word cover the elements or objects listed after the word and their equivalents, without excluding other elements or objects.
[0036] On the one hand, the present invention provides a design method of a Ti65 titanium alloy welding material, comprising the following steps:
[0037] S1: Determine the elements contained in the base material and the content of each element.
[0038] In a specific embodiment, the composition of the parent material is shown in Table 1:
[0039] Table 1 Base material composition (w%)
[0040] Al Sn Zr Mo Si Ta Nb W C Ti 5.5~6.5 3.0~4.5 3.0~7.0 0.2~1.0 0.2~0.5 0.5~2.5 0.2~0.7 0.3~1.2 0.02~0.08 Bal.
[0041] S2: Designing a plurality of groups of welding material compositions with different compositions according to the parent material.
[0042] In a specific embodiment, when designing the welding material composition, the elements contained in the welding material composition are all elements in the parent material except element C. When targeting the parent material shown in Table 1, the welding material composition includes Al, Sn, Zr, Mo, Si, Ta, Nb, W, C, and Ti, and the role of each element in the welding material is as follows:
[0043] Al: has a significant ability to stabilize the α phase and can improve the solid solution strengthening effect;
[0044] Si: Adding a small amount of Si element can significantly improve high temperature creep performance;
[0045] Mo: Adding Mo plays the role of solid solution strengthening and grain refinement. The increase of Mo content can effectively improve the fracture toughness of titanium alloy;
[0046] Sn: The strengthening effect is weak, but it can reduce the hydrogen embrittlement sensitivity of the alloy;
[0047] W: The addition of W element can improve the thermal strength of the alloy to a certain extent;
[0048] Zr: The solid solution strengthening effect is remarkable;
[0049] Nb: The strengthening effect is weak, but adding it to Ti-Al metals can improve plasticity and toughness;
[0050] Ta: The strengthening effect is the weakest. Adding a small amount can improve the material's oxidation resistance and corrosion resistance.
[0051] In a specific embodiment, when designing the welding material composition, the material molecular dynamics, material properties, equilibrium / non-equilibrium phase diagram are simulated and calculated based on software such as Materials Studio, JmatPro, Pandat, etc., so as to obtain the initial content of each element; then, a spectrometer is used to measure the element burnout during the welding process, and the initial content is corrected according to the measurement results.
[0052] S3: using a vacuum non-consumable melting furnace to melt the welding material components to obtain multiple groups of titanium alloy ingots with different compositions.
[0053] In the present invention, a vacuum non-consumable melting furnace is used to melt the welding material components. Compared with other large-scale melting equipment, this method and equipment can greatly reduce energy consumption, so that the present invention can not only greatly reduce material and energy consumption, but also greatly improve welding material melting efficiency.
[0054] S4: processing the titanium alloy ingot into a long strip, opening a groove on the base material, and inserting the long strip into the groove for laser welding.
[0055] In a specific embodiment, the groove is formed by splicing two pieces of base materials with bevels.
[0056] S5: Sampling the samples after laser welding and performing performance tests to obtain the performance of each weld joint, and according to the performance of each weld joint, selecting the welding material composition that is more suitable for the parent material to obtain the Ti65 titanium alloy welding material.
[0057] In a specific embodiment, when performing performance testing, the morphology, grain size and second phase morphology of the weld structure are observed using a metallographic microscope and a scanning electron microscope; the tensile properties and impact toughness of the samples are tested using a universal tensile machine and an impact testing device to obtain the strength, plasticity and toughness values of the weld joint.
[0058] On the other hand, the present invention also provides a Ti65 titanium alloy welding material, which is designed using the design method of the Ti65 titanium alloy welding material described in any one of the above. The designed composition includes, by mass percentage, 6.5-7.5% aluminum, 4.5-5.5% tin, 3.0-7.0% zirconium, 0.5-1.5% molybdenum, 0.2-0.5% silicon, 1.5-2.5% tantalum, 0.5-1.5% niobium, 0.1-1.0% tungsten, and the balance is titanium.
[0059] On the other hand, the application of the Ti65 titanium alloy welding material as described above in Ti65 titanium alloy laser wire welding is also provided.
[0060] In a specific embodiment, when laser wire welding is performed, the speed is 30 mm / s, the power is 5 kW, the defocus is 0 mm, the laser circular swing diameter is 1.5 mm, and the swing frequency is 300 Hz.
[0061] Example 1
[0062] A design method for Ti65 titanium alloy welding material comprises the following steps:
[0063] (1) Determine the elements contained in the base material and the content of each element. The results are shown in Table 1;
[0064] (2) designing welding material composition according to the parent material;
[0065] In this embodiment, according to the parent material, the welding material composition is determined to include Al, Sn, Zr, Mo, Si, Ta, Nb, W, C, and Ti. The JmatPro software is used to simulate and calculate each element. The calculation results are as follows: Figure 1-9 shown.
[0066] from Figure 1-Figure 3 It can be seen that as the Al content in titanium alloy increases, its yield strength, tensile strength and hardness increase accordingly, mainly because Al atoms play a role in solid solution strengthening inside the titanium alloy. Figure 4 From the calculation results of the phase diagram shown, it can be seen that when the Al content reaches 5.6%, the Al atoms reach the saturated solid solubility, and as its content increases, the Ti3Al phase precipitates. When the precipitation of the Ti3Al phase is small, it will further improve the comprehensive performance of the alloy through mass strengthening. However, if the Al content continues to increase, the Ti3Al content will continue to increase and coarsen, resulting in alloy embrittlement and decreased corrosion resistance. Therefore, it is necessary to control the Al content within a reasonable range. According to the simulation results, the initial content of the aluminum alloy is set to 5.9%.
[0067] from Figure 5 It can be seen that with the increase of Zr content, the content of Ti3Al phase continues to decrease and disappear, which may be due to the increase of Zr content, which increases the solid solubility of Al in the Ti matrix. At the same time, the increase of Zr content has no obvious effect on the phase composition of titanium alloy, so the Zr content of 3.5% is selected according to the composition range of the parent material.
[0068] from Figure 6It can be seen that with the increase of Si content, TiZrSi phase, Ti3Al phase and Ti5Si3 phase are precipitated in sequence at the grain boundary, which will lead to material embrittlement. However, the addition of a small amount of Si is beneficial to the high temperature creep resistance of titanium alloy, so the Si content is selected to be 0.4%.
[0069] from Figure 7 It can be seen that when the Mo content exceeds 0.4%, TiZrSi phase will precipitate in the matrix. The increase in Mo content reduces the solid solubility of Si, but less Mo is beneficial to refining alloy grains and improving alloy fracture toughness, so a Mo content of 0.5% is selected.
[0070] from Figure 8 It can be seen that as the Ta content increases, the β phase content increases, and the Ti65 base material is a near-α titanium alloy (the β phase content is 2% to 8%). If there is too much β phase in the weld, its high temperature performance will be poor, so the Ta element content is selected to be 2%.
[0071] from Fig. 9 It can be seen that the change of Sn content has no obvious effect on the alloy phase composition, so 4% Sn content was selected in the base material composition.
[0072] The remaining elements such as Nb and W are trace elements, and their purpose is to improve the high temperature performance and processing performance of the material, so they are not discussed here. In this embodiment, the welding material composition designed based on JmatPro software is shown in Table 2:
[0073] Table 2 Welding material composition (w%)
[0074] type Al Sn Zr Mo Si Ta Nb W Ti JmatPro Design Ingredients 5.9 4.0 3.5 0.5 0.4 2.0 0.3 0.8 Bal.
[0075] Since Al and Sn have low melting points, they are burned off in large quantities during welding. To compensate for the effect of the burning of these elements on weld performance, Al and Sn are added by 1% each on the basis of the composition design in Table 2. The final composition design is shown in Table 3:
[0076] Table 3 Welding material composition (w%)
[0077] type Al Sn Zr Mo Si Ta Nb W Ti Corrected ingredients 6.9 5.0 3.5 0.5 0.4 2.0 0.3 0.8 Bal.
[0078] In addition to the welding material compositions shown in Table 3 as the examples, three other groups of welding material compositions as comparative examples were designed according to Table 3. The results are shown in Table 4:
[0079] Table 4 Welding material composition (w%)
[0080]
[0081]
[0082] (3) using a vacuum non-consumable melting furnace to melt the welding material components to obtain a titanium alloy ingot;
[0083] In this embodiment, the welding material components are melted into a disc-shaped ingot with a diameter of 30 mm and a thickness of about 12 mm. The vacuum non-consumable melting furnace used in this embodiment to melt the welding material components has the following advantages: ① Short melting time, the melting time of one furnace is about 2 hours. ② A large number of components to be melted, one furnace can melt 5 groups of material components. ③ Saving materials, each group of welding material components only needs about 30g of raw materials to melt. ④ Saving energy, compared with other large-scale melting equipment, this method and equipment can greatly reduce energy consumption.
[0084] (4) performing laser welding;
[0085] The titanium alloy ingot is processed into a strip of 1.2×2.5×30mm, and a groove of 0.5×2×80mm is opened on the 2.5×50×80mm parent material. The processed strip welding material is pickled (pickling solution HF:HNO3:H2O=5:12:83, time 5min), and then ultrasonically cleaned in alcohol for 10 minutes after pickling, and then dried at 100℃ for 3 hours. The processed welding material is embedded in the groove formed by the grooves of two parent materials, and it is tightly fitted. Below it is a copper protective back plate that can pass protective gas, and above it is a copper cover plate that can pass protective gas. The assembly gap is covered with rubber and metal plate, the purpose of which is to make the weld shape uniform, and at the same time, high-purity argon is passed to protect the molten pool metal from oxidation during welding. The laser welding process parameters are: speed 30mm / s, power 5kw, defocus amount 0mm, laser circular swing diameter 1.5mm, swing frequency 300HZ.
[0086] (5) Microstructure and mechanical properties testing.
[0087] The samples after laser welding were sampled, and the morphology, grain size and second phase morphology of the weld structure were observed using a metallographic microscope and a scanning electron microscope; the tensile properties and impact toughness of the samples were tested using a universal tensile machine and an impact tester to obtain the strength, plasticity and toughness values of the welded joint; the tensile parameters were: 650°C, 3mm / min, and a parallel section length of 50mm. The weld metallographic structure diagrams of the embodiments and comparative examples 1-3 are shown in FIG. Fig.10 The performance test results are shown in Figure 11-12 As shown in Table 5:
[0088] Table 5 Performance test results
[0089] Sample type Tensile strength / MPa Elongation / % Impact toughness / (J / cm2) Vickers hardness / HV Base Material 882 6.7 10.09 345 Example 879 6.1 9.24 392 Comparative Example 1 875 5.11 8.17 461 Comparative Example 2 852 6.3 6.28 399 Comparative Example 3 811 4.2 5.52 417
[0090] Note: The fracture position of the tensile specimens in Table 5 is located in the parent material.
[0091] From Table 5 and Figure 11-12 It can be seen that the tensile strength of the welded joint of the embodiment is close to that of the base material, and its tensile strength, elongation after fracture and impact toughness of the weld all reach 90% of the relevant properties of the base material; the performance of comparative examples 1-3 is not as good as that of the embodiment.
[0092] In summary, the present invention can design and obtain welding materials that are more suitable for Ti65 titanium alloy laser wire welding. Compared with the prior art, the present invention has significant progress.
[0093] The above description is only a representative embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, uses the above-disclosed technical contents to make some changes or modifications to the embodiments are equivalent embodiments of the present invention. However, any simple modification, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.
Claims
1. A design method for Ti65 titanium alloy welding material, characterized in that: The following steps are involved: S1: Determine the elements contained in the base material and the content of each element; S2: designing a plurality of groups of welding material compositions with different compositions according to the parent material; S3: using a vacuum non-consumable melting furnace to melt the welding material components to obtain multiple groups of titanium alloy ingots with different compositions; S4: processing the titanium alloy ingot into a long strip, opening a groove on the parent material, and inserting the long strip into the groove for laser welding; S5: Sampling the samples after laser welding and performing performance tests to obtain the performance of each weld joint, and according to the performance of each weld joint, selecting the welding material composition that is more suitable for the parent material to obtain the Ti65 titanium alloy welding material.
2. The Ti65 titanium alloy welding material according to claim 1, characterized in that: In step S2, when designing the welding material composition, the elements contained in the welding material composition are all elements in the base material except the C element.
3. The Ti65 titanium alloy welding material according to claim 1, characterized in that: In step S2, when designing the welding material composition, the molecular dynamics, material properties, and equilibrium / non-equilibrium phase diagrams of the material are simulated and calculated according to the software, so as to obtain the initial content of each element; then, the element burnout amount during the welding process is measured using a spectrometer, and the initial content is corrected according to the measurement results.
4. The Ti65 titanium alloy welding material according to claim 3, characterized in that: The software is one or more of MaterialsStudio, JmatPro, and Pandat.
5. The Ti65 titanium alloy welding material according to claim 1, characterized in that: In step S4, the groove is formed by splicing two pieces of base materials with bevels.
6. The Ti65 titanium alloy welding material according to claim 1, characterized in that: In step S5, when performing performance testing, the morphology, grain size and second phase morphology of the weld structure are observed using a metallographic microscope and a scanning electron microscope; the tensile properties and impact toughness of the sample are tested using a universal tensile machine and an impact testing device to obtain the strength, plasticity and toughness values of the weld joint.
7. A Ti65 titanium alloy welding material, characterized in that: The Ti65 titanium alloy welding material is designed by the design method of any one of claims 1 to 6. The designed composition includes, by mass percentage, 6.5-7.5% aluminum, 4.5-5.5% tin, 3.0-7.0% zirconium, 0.5-1.5% molybdenum, 0.2-0.5% silicon, 1.5-2.5% tantalum, 0.5-1.5% niobium, 0.1-1.0% tungsten, and the balance is titanium.
8. Application of the Ti65 titanium alloy welding material as claimed in claim 7 in Ti65 titanium alloy laser wire welding.
9. Application of the Ti65 titanium alloy welding material according to claim 8 in Ti65 titanium alloy laser welding with filler wire, characterized in that: When performing laser wire welding, the speed is 30 mm / s, the power is 5 kW, the defocus is 0 mm, the laser circular swing diameter is 1.5 mm, and the swing frequency is 300 Hz.
Citation Information
Patent Citations
Low-cost titanium alloy welding wire suitable for welding titanium alloy at high temperature of over 520 DEG C
CN101966631A
High-temperature titanium alloy
CN104561656A
TC4 titanium alloy solid welding wire for large-thickness ultra-narrow-gap laser wire filling welding and preparation method thereof
CN112872654A
Short-time high-temperature-resistant titanium alloy material and preparation method thereof
CN114645156A
Design method of aluminum alloy welding wire
CN114888482A
